Studi Kasus Perilaku Psikopat Dalam Tindak Pidana Pembunuhan dari Perspektif Kriminologi - Raharjo, Angga Sandhika; Asmara, Daffi Allegra; Delzanty, Kayla; Talitha, Raisyha; Rosdiana, Hani; Ramadhani, Sherlyta; Setiady, Achmad Hanif Avicenna; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Crime is a complex phenomenon that can be understood from various points of view. In the context of criminology, crime refers to human actions that violate the basic norms that apply in society. In this research, the author conducted a review of previous research. This research uses a normative juridical research method by examining statutory regulations sourced from the Criminal Code, namely the Law that regulates murder as stated in CHAPTER XIX Crimes against Life, namely Articles 338-350 of the Criminal Code. This research emphasizes the criminological implications of the crime of murder committed by psychopaths and the legal resolution.Angga Sandhika Raharjo[1], Daffi Allegra Asmara2, Kayla Delzanty3, Raisyha Talitha4, Hani Rosdiana5, Sherlyta Ramadhani6, Achmad Hanif Avicenna Setiady7, Mulyadi8*[1]Email penulis: 2210611063@mahasiswa.upnvj.ac.id1, 2210611073@mahasiswa.upnvj.ac.id2 2210611172@mahasiswa.upnvj.ac.id3 , 2210611178@mahasiswa.upnvj.ac.id4 . 2210611195mahasiswa.upnvj.ac.id5, 2210611199@mahasiswa.upnvj.ac.id62210611329@mahasiswa.upnvj.ac.id7